Persuasion - Austen, Jane 1775-1817 (Cambridge University Press, 2020)
The accident of death makes Persuasion Jane Austen's final novel. It deserves its position by its innovative treatment of passion and rhetorical style and its development of those themes of memory and time, public and private history, inner and outer lives, language and literature, emotion and restraint that have marked all Austen's work. Where the other works move towards a new symbolic and physical home for the heroine, Persuasion begins with her ejection and ends with her understanding that home is not a place at all but an ambiance and an acceptance of change. This volume, first published in 2006, provides comprehensive explanatory notes, an extensive critical introduction covering the context and publication history of the work, a chronology of Austen's life and an authoritative textual apparatus. This edition is an indispensable resource for all scholars and readers of Austen